2012
DOI: 10.5402/2012/763046
|View full text |Cite
|
Sign up to set email alerts
|

Switchgrass (Panicum virgatum L.) Cultivar Adaptation, Biomass Production, and Cellulose Concentration as Affected by Latitude of Origin

Abstract: Ten cultivars of switchgrass (Panicum virgatum L.) of northern and southern origins that had demonstrated adaptation to North Dakota were evaluated for biomass production, cellulose concentration, and nutritive value in the southern Canadian prairie region: Saskatchewan and Manitoba. In this region, cultivars adapted to northern latitudes present interest for biomass production. Latitude of origin of the cultivars was positively correlated to stand density (r = 0.83, P < 0.01), biomass production (r = 0.69, P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…This might indicate that SG responded better to favorable conditions compared to BBS. Similarly to our results, Jefferson [55] reported greater yield potential for SG across a latitudinal gradient compared to other species. However, the differences in yields among mixtures were not significant.…”
Section: Mixture Composition and Yieldssupporting
confidence: 90%
“…This might indicate that SG responded better to favorable conditions compared to BBS. Similarly to our results, Jefferson [55] reported greater yield potential for SG across a latitudinal gradient compared to other species. However, the differences in yields among mixtures were not significant.…”
Section: Mixture Composition and Yieldssupporting
confidence: 90%
“…This result reveals that plants tend to show optimal growth performance near where they have been established and persisted. Similar results have been reported by Jefferson and McCaughey [48] who reported that latitude of origin of a switchgrass ecotype was positively correlated to biomass production.…”
Section: Discussionsupporting
confidence: 79%
“…Growth rate, photoperiodism, heat, and cold or freezing tolerance regulate adaptation of SWG populations (Casler et al 2007). The latitude of origin has a large impact on SWG yield potential and ability to survive in extreme environment (Castler et al 2007;Jefferson & McCaughey 2012). In general, SWG varieties grown too far north (from the latitude of origin) will not flower or will flower later and will not mature before onset of winter.…”
Section: Introductionmentioning
confidence: 99%